2017
DOI: 10.1007/s00701-017-3345-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and factors determining the outcome of dorsal root entry zone lesioning procedure (DREZotomy) in the treatment of intractable pain syndrome

Abstract: MDT is an effective procedure for treatment of intractable pain in well-selected patients, particularly in cases with brachial plexus avulsion pain. Injury of the spinal nerve root (brachial plexus avulsion and cauda equina injury) was associated with good average pain relief and pain freedom, and electrical pain and lower number of painful dermatomes were associated with good maximal pain relief. The results are useful in the selection of candidates for DREZotomy and prediction of surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…30 Surgical ablation of the DREZ destroys and thereby nullifies aberrant nociceptive processing that gives rise to BPA pain. Since its origins in the 1970s, 15,31 DREZ lesioning has been attempted for relief of an aetiologically diverse collection of pain syndromes: spinal cord injury [32][33][34] ; cauda equina injury 32,[35][36][37] ; conus medullaris or lumbosacral plexus injury 30,36,38,39 ; phantom limb pain 32,33,40,41 ; post-herpetic neuralgia 33,[40][41][42] ; syringomyelia 41 ; complex regional pain syndrome 32,33 ; cancer-or radiation-induced pain 32,34,40 ; and spasticity 2,40 . Nowadays, although DREZ lesioning is occasionally used for these alternative pathologies, its primary indication is for BPA deafferentation pain due to more favourable patient outcomes.…”
Section: Role Of Drez Lesioning In Bpamentioning
confidence: 99%
“…30 Surgical ablation of the DREZ destroys and thereby nullifies aberrant nociceptive processing that gives rise to BPA pain. Since its origins in the 1970s, 15,31 DREZ lesioning has been attempted for relief of an aetiologically diverse collection of pain syndromes: spinal cord injury [32][33][34] ; cauda equina injury 32,[35][36][37] ; conus medullaris or lumbosacral plexus injury 30,36,38,39 ; phantom limb pain 32,33,40,41 ; post-herpetic neuralgia 33,[40][41][42] ; syringomyelia 41 ; complex regional pain syndrome 32,33 ; cancer-or radiation-induced pain 32,34,40 ; and spasticity 2,40 . Nowadays, although DREZ lesioning is occasionally used for these alternative pathologies, its primary indication is for BPA deafferentation pain due to more favourable patient outcomes.…”
Section: Role Of Drez Lesioning In Bpamentioning
confidence: 99%
“…The final study list included 31 papers, all of which were case series ( 6 , 7 , 10 , 12 36 ) and case reports ( 37 39 ). No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Radiofrequency lesioning was used in 17 studies; Samii et al initially used cordotomy electrodes to perform the DREZ lesioning, but later reported switching to radiofrequency electrodes ( 12 ). Thermal coagulation using bipolar cautery was used in 8 studies ( 6 , 23 , 26 , 28 , 31 , 36 , 38 , 39 ). In one study, Sindou et al reported performing sharp incisions in the dorsolateral sulcus followed by dot coagulation using bipolar cautery ( 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…0:59 Our data share similar results with other authors. [1][2][3][4][5] The dorsal DREZotomy, devised for pain due to traumatic spinal cord injury, is no longer performed because it is ineffective. The best results are obtained with the lumbar DREZ for monolateral or bilateral avulsive injury of the lower lumbar roots, namely L5 and S1.…”
Section: Transcriptmentioning
confidence: 99%